OFR-35-79 Development Of New Bond Release Criteria For Surface Coal Mines In The Eastern And Interior Coal Provinces Of The United States - William M. Knuth (The National Institute for Occupational Safety and Health (NIOSH), 1978)
This study involved a review of bonding and bond release practices in the states of the Eastern and Midwestern Coal Provinces. Data was collected from regulatory authorities and site visits to document the bonding and release procedures in the states related to achieving successful reclamation. The regulations related to PL95-87 were reviewed. The analysis included suggested modified or new bond release criteria, a review of applicable bond release inspection techniques was prepared, a conceptual graduated bonding system and incentive procedures for reclamation of surface mine sites to alternative or higher land uses. A number of conclusions and recommendations for further research were included. A detailed bibliography and a glossary are included in the report.